2003
DOI: 10.1023/a:1025412509730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valspodar on the pharmacokinetics of unbound paclitaxel

Abstract: The aim of this multicenter study was to determine whether valspodar (Amdray; code designation, SDZ PSC 833), a potent P-glycoprotein (P-gp) inhibitor, affects the pharmacokinetics of unbound paclitaxel (Cu). Data were obtained from 31 patients with advanced breast cancer. Thirteen patients were treated with paclitaxel alone (3-h infusion at 175 mg/m2) and another 18 received paclitaxel (3-h infusion at 70 mg/m2) in combination with a 21-day cycle of oral valspodar (5 mg/kg given four times a day) starting 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Repopulation of tumor cells has been shown to occur in regions far from blood vessels [29], and it is important to consider factors that affect the distribution of chemotherapeutic agents in solid tumors. Numerous clinical trials evaluating the effects of verapamil or valspodar in combination with chemotherapeutic agents such as doxorubicin, vincristine, dexamethasone, cyclophosphamide, paclitaxel have shown that patients given concurrent administration of PgP inhibitors with chemotherapeutic agents have an increased toxicity and show modest or no increase in survival [45-49]. These results provide insight into an important limitation of PgP inhibitors and this principle is likely to be applicable to other membrane-based drug efflux proteins such as multiple drug resistance protein-1 (MRP-1) and suggest the importance of considering drug distribution in the design and development of novel treatment strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Repopulation of tumor cells has been shown to occur in regions far from blood vessels [29], and it is important to consider factors that affect the distribution of chemotherapeutic agents in solid tumors. Numerous clinical trials evaluating the effects of verapamil or valspodar in combination with chemotherapeutic agents such as doxorubicin, vincristine, dexamethasone, cyclophosphamide, paclitaxel have shown that patients given concurrent administration of PgP inhibitors with chemotherapeutic agents have an increased toxicity and show modest or no increase in survival [45-49]. These results provide insight into an important limitation of PgP inhibitors and this principle is likely to be applicable to other membrane-based drug efflux proteins such as multiple drug resistance protein-1 (MRP-1) and suggest the importance of considering drug distribution in the design and development of novel treatment strategies.…”
Section: Resultsmentioning
confidence: 99%
“…TKIs can possibly be exploited to improve pharmacokinetics or overcome resistance to chemotherapeutics that are substrates of ABC drug transporters in cells, tissues or tumors that express high levels of these transporters. As discussed above, a number of studies have already demonstrated that modulation of ABC transporters by inhibitors of these transporters in cancer chemotherapy may also significantly modify the pharmacokinetic and toxic profiles of anticancer drugs (Darvari and Boroujerdi, 2005; Sparreboom et al, 1999; ten Tije et al, 2003). This suggests that a combination of TKIs with cytotoxic anticancer drugs that are substrates of ABC transporters, especially P-gp and ABCG2, may offer an advantage for treating the drug-resistant cancers.…”
Section: Exploiting Tkis As Inhibitors Of Abc Transporters-a Perspmentioning
confidence: 99%
“…In order to accommodate this pharmacokinetic interaction in valspodar trials, anticancer drug doses were reduced by 25–50% [44,45]. However, because of interpatient variation in CYP3A4 metabolism, some patients were underdosed and others overdosed [46,47]. A Phase III CALGB (Cancer and Leukemia Group B) trial using valspodar in previously untreated AML patients over age 60 was closed early due to excessive mortality in the experimental arm during induction [45].…”
Section: Clinical Trialsmentioning
confidence: 99%